Does a Feedforward Orientation Provide Competitive Advantages Under Disruptive Conditions? A Review of Control Literature with an Illustrative Case - Rajaram Veliyath (Administrative Sciences)
This paper identifies the salient features of feedforward control and the advantages that it provides vis-à-vis feedback control. These advantages are especially salient in strategic control situations and also during periods of environmental turbulence and extreme strategic discontinuity. Consciously adopting a feedforward orientation in organizational strategic management processes could enhance an organization’s competitive advantages and potentially lead to sustainable, superior performance. Additionally, broadening the conceptual definition of feedforward (from its cybernetic origins) to also include strategic foresight might also enable organizations to develop dynamic capabilities. The example of Zara, a leader in ‘fast-fashion’ retailing, is presented as an example of how feedforward attributes can be identified, inculcated, and ingrained/retained as organizational attributes that become a part of an organization’s DNA. Moreover, when severe external environmental disruptions inevitably erode an organization’s resource bases and pose an existential threat to the organization’s survival, such a feedforward orientation could be the catalyst for coping, adapting, and developing new dynamic capabilities. These new capabilities can not only help organizations to counter newly emergent threats and survive, but also help them to dynamically cultivate and develop newer sources of competitive advantages.